Balancing Burden and Benefit: Non-Prescribed Use of Employer-Issued Mobile Devices - Schwartz, Ariel; Bhavsar, Mohini; Cutrell, Ed; Donner, Jonathan; Densmore, Melissa (Proc. ICTD 2013, Dec 07-10 2013, Cape Town, South Africa, 2013)
Mobile devices are increasingly powerful and flexible tools for computing and communication. When ICTD workers are given a mobile phone 'for work', what else do they do? And to what extent can or should an employer shape that use? This note presents research in progress, focused on rules that development projects impose to govern use of mobile devices. This work maps these rules against actual instrumental (work-related, non-prescribed) and non-instrumental (personal) device use, and enforcement of these rules, in eight projects using a popular mobile-based job aid, CommCare. We present early insights from qualitative analysis of two such deployments in India identifying a range of often conflicting policy choices that affect device use for project mission and/or professional and personal empowerment. We explore tradeoffs for morale, work quality, mission, and device integrity. We identify user remote availability, soft intimidation, and validation as mechanisms to shift authority and credibility of information sources. The implications of our findings are increasingly important as governments and NGOs arm frontline workers with mobile devices as tools to improve service delivery.